CAN ARTIFICIAL INTELLIGENCE FOSTER L2 LEARNING? INVESTIGATING ITS IMPACT ON BEHAVIORAL, COGNITIVE, AND EMOTIONAL ENGAGEMENT IN EFL CONTEXTS - Dwita Laksmita Rachmawati; Nirwanto Maruf; Hidayatul Badi'ah; Agus Mulyadi (University of Kuningan, 2026)
This study investigates the impact of Artificial Intelligence (AI) on students’ behavioral, cognitive, and emotional engagement in an English as a Foreign Language (EFL) context. Employing a mixed-methods explanatory sequential design, the study involved 70 undergraduate students at a private university in Indonesia. Quantitative data were collected through a structured questionnaire, while qualitative data were obtained from semi-structured interviews and reflective responses. The findings reveal that AI positively influences all dimensions of engagement, with the strongest effect observed in behavioral engagement, followed by cognitive engagement, and a more variable impact on emotional engagement. Among the AI tools examined, adaptive learning platforms and chatbot interactions were found to be more effective than writing assistants. Correlation analysis confirmed significant positive relationships between AI use and all engagement dimensions. However, qualitative findings indicate challenges such as over-reliance and unclear feedback. The study highlights the importance of strategic AI integration to maximize engagement in EFL learning.